2014
DOI: 10.1177/230949901402200117
|View full text |Cite
|
Sign up to set email alerts
|

Grafted Tendon Healing in Femoral and Tibial Tunnels after Anterior Cruciate Ligament Reconstruction

Abstract: After ACL reconstruction, the tendon-to- bone healing in the FIZ of the tibial tunnel was faster than that of the femoral tunnel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 20 publications
(17 reference statements)
1
17
1
Order By: Relevance
“…In the current study, the center of the femoral tunnel was located at 25.3% from the deepest subchondral contour of the lateral femoral condyle and at 31.8% from Blumensaat's line. This result indicates that our femoral tunnels were located slightly posterior and shallower, compared the placement that was reported by Piefer et al However, this result appears to be reasonable for tendon-bone healing, as the tendon-bone junction is revitalized on the anterior side of the femoral bone tunnel [24] .…”
Section: Discussioncontrasting
confidence: 33%
“…In the current study, the center of the femoral tunnel was located at 25.3% from the deepest subchondral contour of the lateral femoral condyle and at 31.8% from Blumensaat's line. This result indicates that our femoral tunnels were located slightly posterior and shallower, compared the placement that was reported by Piefer et al However, this result appears to be reasonable for tendon-bone healing, as the tendon-bone junction is revitalized on the anterior side of the femoral bone tunnel [24] .…”
Section: Discussioncontrasting
confidence: 33%
“…In our study, grafts gradually remodeled within 2 years after ACLR, shown by the SNQs of intra-articular and intraosseous grafts peaking at 6 months postoperatively and then gradually decreasing at 12 and 24 months. To eliminate the influence of background noise, the SNQ 12,30,44,49 has been adopted as a more precise parameter than signal intensity to measure graft quality using MRI in which a lower SNQ reflects better graft maturity. 44 Increases in femoral graft SNQs at 6 months postoperatively and decreases at 2 years have been previously found in both human and animal studies.…”
Section: Discussionmentioning
confidence: 99%
“…Intraobserver and interobserver reliability values for the SNQ were 0.876 and 0.935, respectively. The SNQ 12,30,44,49 has been adopted as a measurement for analyzing graft quality in which a lower SNQ reflects better graft maturity. 44 At 1 day postoperatively, the mean SNQ of the femoral intraosseous graft was 3.476 6 0.344, and that of the intra-articular graft was 3.375 6 0.763.…”
Section: Graft Snq Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Rodeo et al 18 used animal experiments to prove the existence of GTM, reporting that the amplitude of GTM had a positive correlation with the width of graft-bone interface and a negative correlation with the healing progress. Nakase et al, 16 using magnetic resonance imaging (MRI) for follow-up of patients who received ACL reconstruction, found differences in healing for different portions of the graft not only longitudinally but also transversally. These investigators suggested that the windshield wiper effect caused anterior-posterior GTM that impaired the healing process.…”
mentioning
confidence: 99%